A three-stage decision framework for multi-subject emotion recognition using physiological signals - Jing Chen; Bin Hu; Yue Wang; Yongqiang Dai; Yuan Yao; Shengjie Zhao (2016 IEEE International Conference on Bioinformatics and Biomedicine (BIBM), 2016)
This paper investigates the potential of physiological signals as reliable channels for multi-subject emotion recognition. A three-stage decision framework is proposed for recognizing four emotions of multiple subjects. The decision framework consists of three stages: (1) in the initial stage, identifying a subject group that a test subject can be mapped to; (2) in the second stage, identifying an emotion pool that an instance of the test subject can be assigned to; and (3) in the final stage, generating the predicted emotion from the given emotion pool for the test instance. In comparison with a series of alternative methods, the high accuracy of 70.04% achieved by our proposed method clearly demonstrates the potential of the three-stage decision method in multi-subject emotion recognition.